Contribuição à taxonomia do gênero Psammobatis Günther, 1870 (Chondrichthyes, Rajidae): caracterização das espécies do subgrupo I de McEachran (1983) com base em padrões de coloração e espinulação - Paragó, Cristina Luiza Dalia Pereira (2001)
The genus Psammobatis Günther, 1870 is a South American endemic represented in both the Atlantic and Pacific coasts of the continent. It has been recently reviewed by McEACHRAN (1983), who divided the genus in two monophyletic groups. Subgroup I, composed of P. bergi Marini, 1932; P. glansdissimilis McEachran, 1983; P. lentiginosa McEachran, 1983 and P. rutrum Jordan, 1890 includes species which occur off the coast of southeastern/southern Brazil, Uruguay and northern Argentina. Subgroup II is formed by P. normani McEachran, 1983; P. parvacauda McEachran, 1983; P. rudis Günther, 1870 and P. scobina (Philippi, 1857), the distribution of which is restricted to shelf waters off the southern coasts of Argentina and Chile, the latter in the eastern South Pacifíc. Misidentifications among species of subgroup I are frequent, particularly between individuals of P. extenta and P. rutrum. These two species are remarkably similar, the separation of adult specimens being nevertheless possible by the presence of thorns in the spermatic duct of the mixopterygia. Since this character can not be observed in young males and females, the identification of specimens of the above species is often problematical. Problems related to the identification of the species included in subgroup I of McEACHRAN (1983) were reviewed, and new characters were defined in order to turn practical the separation of the four species of the subgroup by means of the examination of external characters. An identification key for the species of the subgroup based on external characters is presented, and its use turns possible the ready identification of young and adults of both sexes, both in the laboratory or in the field.